Lignin Source and Structural Characterization - Sun, Run‐Cang (ChemSusChem, 2020)
Lignin is a primary component of lignocellulosic biomass and an underutilized feedstock in the growing pulping and biofuel industries. Currently, over 50 million tons of industrial lignin are produced annually from pulping and bioethanol processes in the world. Around 95 % of industrial lignin is burned as fuel in heat and power plants due to its complicated, destructive, and condensed structures hindering direct industrial utilization, while the remaining 5 % of lignin is used for potential applications, such as additives, binders, dispersants, and surfactants, through modification. Meanwhile, different biorefinery processes also produce a considerable amount of lignin with various structural features and properties. The development of technologies for its structural characterization is currently desirable for lignin valorization, which will improve the techno‐economics of applications of lignins in industries. Sources and structures: Lignin is a primary component of lignocellulosic biomass and an underutilized industrial feedstock. Currently, about 95 % of industrial lignin is burned as fuel in heat and power plants because its structure hinders direct industrial utilization, and 5 % is used for applications after modification. Hence, the development of methods for its structural characterization are desirable for lignin valorization, which will improve the techno‐economics of industrial applications of lignins.